(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
This article explores the dynamic nature of the English lexicon, focusing on how words emerge, evolve, and eventually fade from active use. By examining historical shifts, borrowing mechanisms, technological impacts, and the natural process of obsolescence, the study illustrates that English is an adaptable ecosystem. The article analyzes the mechanisms of word formation and semantic shifts that allow the language to mirror human progress and cultural integration.